'His visa is made of rubber': tactics, risk and temporary moorings under conditions of multi-stage migration to Australia. (24th March 2021) - Roberts, Rosie
ABSTRACT: This article examines the narratives of two Venezuelan migrants who have engaged in multi-stage migration practices in order to optimise their long-term living options in Australia. I show how they deploy a range of tactics to negotiate risk and uncertainty under the spatial, temporal and institutional conditions of temporary migration programs by moving to regional areas, drawing on friendship networks and continuously responding to shifting immigration policy. I argue that time spent on temporary visas is actively and intentionally used by migrants in order to create future migration possibilities and security for themselves in contexts where migration outcomes can be unpredictable. As temporary migrants they are subject to policies designed to meet the needs of global capital and skills shortages but they are also reasoning individuals who tactically pursue opportunities, put down roots and continually evaluate and readjust their plans and fall back positions, even within a relatively limited range of choices.